Research on the Dilemma and Pathways for High-Quality Development of the Population in Western China - Zhang, Kaibo; Huang, Yue (Journal of Social Science and Humanities, 2025)
The population challenge has consistently represented a comprehensive, enduring, and strategic issue confronting China. Western China, serving as a crucial security bulwark within the nation, holds its high-quality population development in close relation to national unity, social stability, and national security. Grounded in the realities of Western China’s economic and social progress, this paper delves into the obstacles impeding the high-quality development of Western China’s population, considering factors such as the natural environment, economic and social development, and the current demographic landscape. It then proposes the following effective strategies: bolstering the construction of the public service system, enhancing the medical service infrastructure, and fortifying disaster prevention mechanisms; fostering the internal driving forces of economic growth, reinforcing scientific and technological innovation, and cultivating new, high-quality productivity tailored to the plateau’s unique conditions; and optimizing the population structure, promoting balanced regional development, and maximizing the benefits of talent utilization.